THE IMPLEMENTATION OF MIND MAPPING STRATEGY ON STUDENTS’SPEAKING ABILITY (LITERATURE STUDY) - Ahmad Yanuar Syauki; Bendra Wardana; Sulistiawati Maulina (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2021)
This objective of the study is to improve students' speaking skills through the implementation of the mind mapping strategy. This study uses a literature study consisting of several sources, such as primary sources from books and secondary sources from manuscripts and journals. The results of the research that the author did from several sources studied by Asrifal Mirza increased the score which post-test experiment was higher (mean 69.05) while the mean of post-test control class was 57.11. Researcher tati rahmawati on his journal So it can be seen from the result of the first cycle, in this test we can know that the highest score was 88, the lowest score was 56 and the average of students' score was 71.7, for the second cycle the highest score was 100, the lowest score was 76 and the average of the students' score was 80.9. It showed that there was significant improvement of students' skills in speaking. And from the overall results of previous studies that examined theoretically, it can be concluded that the implementation of mind mapping strategy had a significant effect